Relationship between total area planted and palm oil price towards production of Malaysian palm oil/ Errie Azwan Abdu Razak - Abdu Razak, Errie Azwan (Faculty of Business and Management, 2010)
This paper examines the relationship between the production of Malaysian palm oil and its determinants; total area planted and palm oil price using Johansen multivariate cointegration analysis based on ECM. The relationship among those variables is investigated using annual data from 1972 to 2008. The researcher focused on that particular period of study because the production of Malaysian palm oil had been accelerating at a rapid rate in the past, especially prior to 1980s. After having completed the analysis by using VECM, the findings shows that both independent variables; total area planted and palm oil price have negative relationship towards production of Malaysian palm oil. In long run relationship, palm oil price is influences the production of palm oil in Malaysia. On the other hand, Granger causality resulted that there is no causality relationship between total area planted and production of Malaysian palm oil in short run relationship while palm oil price and production of Malaysian palm oil have unidirectional causality relationship. It means that, the production of Malaysian palm oil “granger cause” the palm oil price.